PENGARUH BRAND AFFECT DAN BRAND QUALITY TERHADAP CONSUMER’S BRAND EXTENSION ATTITUDE MELALUI BRAND LOYALTY PELANGGAN REEBOK DI SURABAYA - SETIONO, SHERLY ELISABETH (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The purpose of this study was to test the brand affect and brand quality on consumer's brand extension on brand loyalty through customer reebok in surabaya. This study the analysis of SEM analysis (Structural Equation Modeling) to analyze the brand affect and brand quality to the consumer's brand extension attitude through brand loyalty while sampling in this study using purposive sampling method, so that the samples used in this study of 150 respondents. The results Brand Affect influence on Brand Loyalty in accordance with the research Jahangir, et al (2009), Brand Quality effect on Brand Loyalty consistent with Anwar dan Gulzar (2011), Brand Loyalty effect on the Consumer's Brand Extension Attiude consistent with Jahangir, et al ., (2009), Brand Loyalty as an intervening variable in the influence of Brand Affect on Consumers' Brand Extension Attitude consistent with Anwar dan Gulzar (2011), Brand Loyalty as an intervening variable in the influence of Brand Quality on Consumer's Brand Extension Attitude does not support research Anwar dan Gulzar (2011), Brand Loyalty as an intervening variable in the influence of Quality Brand and Brand Affect on Consumers' Brand Extension Attitude consistent with Anwar dan Gulzar (2011).